การพัฒนาหุ่นจำลองต้นแบบสำหรับฝึกตรวจช่องท้อง - ประจันเขตต์ องค์อร; ประสิทธิเวชชากูร อายุพร (Journal of The Royal Thai Army Nurses, 2017)
บทความฉบับนี้ มีวัตถุประสงค์เพื่อเผยแพร่ความรู้เกี่ยวกับการพัฒนา "หุ่นจำลองต้นแบบสำหรับฝึกตรวจช่องท้อง" ที่ผู้เขียนได้คิดค้นประดิษฐ์ขึ้นเพื่อเป็นสื่อช่วยสอนในการฝึกตรวจช่องท้องของนักเรียนพยาบาล และบุคลากรสาธารณสุขที่สนใจฝึกทักษะการตรวจระบบช่องท้องให้มีความชำนาญ สามารถวินิจฉัยแยกโรคได้เนื่องจากคุณสมบัติของหุ่นจำลองนี้ สามารถใส่น้ำและลมเข้าไปในช่องท้องได้ จึงมีความแตกต่างจากหุ่นที่มีอยู่ในปัจจุบันและมีต้นทุนที่ต่ำกว่าการสั่งซื้อหุ่นจากต่างประเทศ เพราะมีวัตถุดิบหลักที่ใช้ คือ ยางพารา ซึ่งเป็นวัตถุดิบที่มีมากในประเทศราคาถูก และหาได้ง่าย เป็นการเพิ่มมูลค่าให้กับยางพาราไทย สอดคล้องกับหลักปรัชญาเศรษฐกิจพอเพียง และนโยบายของรัฐบาลปัจจุบัน Development of The Prototype Model for Practicing Abdominal Examination This academic article aim to disseminate knowledge of development “The Prototype Model for Practicing Abdominal Examination” which invented for practicing abdominal assessment among army nursing students and health professionals who interested in enhancing their skills in abdominal assessment and differential diagnoses in Gastrointestinal disease. Due to the features of the model can enter the water and wind into the abdominal cavity. It is different from the current models and lower cost than other imported models. Because, this models used latex as the major raw material which is very cheap and readily available in Thailand. This leads to increasing the value of Thai rubber. Compliance with the suffciency economy philosophy and current government policies. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">